Does return dispersion explain the accrual and investment anomalies? - Chichernea, Doina C.; Holder, Anthony D.; Petkevich, Alex (Journal of Accounting and Economics, 2015)
Recent research shows that high return dispersion (RD) is associated with economic conditions characterized by high discount rates, which are not conducive to growth and investment. We propose that RD risk can explain the accrual and investment anomalies. We conduct asset-pricing tests that include RD as a potential risk factor and show that low-accrual and low-investment firms have significantly higher exposure to the risk captured by RD. RD significantly explains future returns and the excess returns to accrual and investment hedge portfolios shrink in magnitude and become insignificant during periods of low RD. We conclude that risk explains the accrual and investment anomalies.